The relationship between self-control and altruism in the light of discounting literature - Jerzy Osiński; Adam Karbowski; Jan Rusek (Polish Psychological Bulletin, 2017)
On the basis of literature on delay discounting, potential mechanisms of relations between self-control and altruism are considered. The discussed possibilities are: cause-and-effect relationship (self-control enabling sacrificing immediate benefits caused by selfish behaviour in favor of future benefits associated with altruism, e.g. reciprocation), common mechanism (ability to learn behavioural patterns covering longer time periods), role of intelligence as a factor related both to self-control and altruism, and role of psychological distance (the idea of extended self and construal level theory). Relations between described perspectives are pointed out, and directions for further research are suggested.
Keywords: D01; D03; 330; Altruism; Cooperation; Delay; Self-control; Discounting